Community stewardship to protect coastal and freshwater ecosystems–pathways between recreation and stewardship intentions - Angela J. Dean; Konrad Uebel; Tracy Schultz; Kelly S. Fielding; Emily Saeck; Helen Ross; Victoria Martin (People and Nature, 2024)
Abstract Strengthening community engagement in stewardship can help to improve management of coastal and freshwater environments (blue spaces). Research suggests that recreational users of natural areas may be more willing to engage in stewardship. However, little research at a population scale has examine how recreation experiences shape psychological ingredients for stewardship. We surveyed 3271 residents of South East Queensland, Australia and quantified willingness to engage in blue space stewardship. We then quantified frequency of different types of blue space recreation, perceptions about threats to blue spaces (threat appraisal) and protective actions (coping appraisal), and satisfaction with blue spaces. We then examined pathways from recreation to stewardship intentions using mediation analysis. Results show that many types of recreation were associated with stewardship intentions. Specifically, higher frequency of social activities and nature‐appreciation activities were associated with greater intentions for individual stewardship (e.g. picking up litter, reducing use of household chemicals). Higher frequency of social activities, nature appreciation, exercise and fishing/boating was associated with stronger intentions for collective stewardship (e.g. attending a public meeting or riparian management event) Mediation analysis showed that most forms of recreation did not influence perceptions about severity of threats to blue spaces. Rather, the relationships between recreation and stewardship were mediated by greater place satisfaction, perceived vulnerability to blue space degradation, and feeling more able to contribute to waterway protection (efficacy). These findings indicate that many types of recreation (not just nature appreciation activities) can be a foundation for engaging in nature stewardship, and reinforce the importance of building efficacy when promoting stewardship. The finding that both place satisfaction and perceived vulnerability to environmental degradation suggests that there may be an optimal motivational window for stewardship: people need to connect a place with positive experiences, and have some recognition of a potential threat, but where the potential threat has not yet eroded the natural values of a place. Read the free Plain Language Summary for this article on the Journal blog.